Análisis del nivel de información que ofrecen los medios de comunicación Social en el Cantón La Mana - Ulloa Torres, Johanna Maricela (2015)
Communication processes are part of the day to day in modern societies, transforming them into basic pillars of human relations. In our world today it is obvious the interest and study of these, for this reason, it is necessary the analysis of this phenomenon. As sources of study for its analysis is the canton La Maná, where the inhabitants are people who have an identity of its own, it maintains a culture of work in the field and the trade, are people who share with the community, many of them persons of humble surrounding sectors; all need to communicate, express their ideas, be known and recognized by the value that identifies them as such……